Employment : Focus on housework / Wee Chong Hui - Wee, Chong Hui (Institut Teknologi Mara Cawangan Sarawak, 1989)
My mother was a nurse. When she gave birth to me, she quit her job to take care of her first-born. She became "unemployed". Two years later, my brother was bom. Soon after, we left for Sabah to where my father was transferred. We returned to our hometown. My little brother was old enough not to demand my mother's constant attention. So my mother decided to leave us in grandma's care. My mother resumed nursing but resigned after the birth of my sister. My mother has been cooking and washing for all 13 of us and my father for the last 15 years. And the statistics department registers her as "unemployed." - A Son.